Sustainable Methods for Improving the Feeding Patterns of Undergraduate Student of Michael Okpara University of Agriculture, Umudike, Abia State, Nigeria. (Global Journal of Medical Research, 2015)
The study identified the sustainable strategies for improving the feeding patterns of undergraduate students of Michael Okpara university of Agriculture, Umudike. The purpose of the study was to identify the feeding patterns adopted by the students and to identify the sustainable strategies for improving the feeding patterns of these students. The study adopted a survey research design. The population of the study was made up of 14,779 students of the various colleges and levels. Data was collected using well structured questionnaire developed through an extensive literature review. Purposive random sampling techniques were used to select 389 respondents used for the study. Data were analyzed using means and percentages. Results showed that most of the students agreed that they skipped meals as a result of habit formed about foods and they obtain their foods from fast food centres.
Keywords: sustainable; strategies; feeding; patterns and undergraduates